Velocity‐free formation control for omnidirectional mobile robots with input saturation - Jia, Yuxin; Jia, Yingmin; Gong, Kai; Zheng, Wenhao (IET control theory & applications, 2023)
This paper presents a command‐filter‐based formation control scheme for the leader‐follower omnidirectional mobile robots (OMRs) subject to the absence of the velocity measurements, input saturation and unknown bounded disturbances. First, an adaptive velocity observer is designed based on a novel state transformation of the OMR dynamics. Then, a finite‐time command filtering strategy is proposed, where the Levant filter is used to estimate the time derivative of the virtual control law, and an error compensator with finite time convergence is constructed to eliminate the filtering error correspondingly. Moreover, the anti‐saturation module and adaptive law are designed to attenuate the influence caused by input saturation and external disturbances. The proposed control scheme can ensure that all signals of the closed‐loop system including the formation error are uniformly bounded, and the effectiveness is verified by the simulations results. This paper proposes a formation control scheme for the leader‐follower omnidirectional mobile robots. By means of the designed velocity observer based on a novel state transformation, the finite‐time command filtering strategy and the anti‐saturation module, the closed‐loop system can ensure that all signals are uniformly bounded, even subject to the absence of the velocity measurements, input saturation and external disturbances.